The Strategic Approach to Recruitment and Selection at WIKA Rekayasa Konstruksi: Implication and Recommendation - Gunawan, William Ben; Oktavia, Yesica Dyah; Budiman, Arif Harry; Diptawibowo, Narendra Diwangkara (Department of Public Administration, Parahyangan Catholic University, 2025)
Recruitment and selection are critical components of human resource management, as they directly influence an organization’s ability to attract, identify, and retain top talent in a competitive industry. Despite extensive literature on recruitment strategies, limited research examines the integration of these practices with long-term organizational goals in Indonesian construction firms. This study explores the strategic recruitment and selection processes at WIKA Rekayasa Konstruksi (WRK), a subsidiary of PT Wijaya Karya Tbk (WIKA), and their impact on the quality of human resources as well as organizational performance. This study seeks to address this gap by analyzing WRK’s methodologies, assessing their effectiveness, and offering strategic recommendations for improvement. This research employed a descriptive qualitative approach, the data was collected through interviews with a key informant, WRK’s Senior Manager of the Human Capital division. The findings reveal that while WRK employs comprehensive methods—such as competitive salary offerings, digital recruitment platforms, and multi-stage evaluations—there is room for improvement in aligning recruitment practices with strategic objectives and enhancing transparency in cost-related communication during post-selection stages. This research contributes to the academic discourse by highlighting best practices and challenges in recruitment within the construction sector, offering actionable insights for organizations aiming to optimize human resource management strategies.